From physics of polar aurora to changes of the fundamental approaches to the physics of the magnetospheric processes - Antonova, Elizaveta E. (Frontiers in Astronomy and Space Sciences, 2022)
One of the main problems of modern magnetospheric physics is the lack of a self-consistent explanation of the main physical processes based on the laws of plasma physics. Among all the traditionally studied phenomena, the polar aurora stands out for being key to our understanding of several magnetospheric processes. In this manuscript, I would like to share with the younger generation my view about main auroral processes which I have developed during my career over the past fifty years.